Storage-stable solid rubber epoxy adducts
By reacting solid adduct with a low acid content with epoxy resin to form a solid adduct, the brittleness of epoxy thermosetting resin materials and liquid CTBN storage stability are solved, and the effect of enhancing fracture toughness and storage stability is achieved.
Patent Information
- Application Number
- CN202380051356.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-08
- Filing Date
- 2023-07-10
- Publication Date
- 2025-02-18
Smart Images

Figure CN119487098A_ABST
Abstract
Description
[0001] Priority claim
[0002] This application claims the benefit of the priority date of U.S. Provisional Application Serial No. 63 / 359,513, filed on July 8, 2022. The contents of that application are hereby incorporated by reference herein in their entirety and for all purposes. Technical Field
[0003] The present teachings generally relate to storage-stable, solid carboxylated nitrile rubber-epoxy resin adducts that can be used in epoxy thermoset resins. More specifically, solid epoxy resin adducts from low acid percentage carboxylated nitrile rubbers can be storage-stable and are useful toughening agents in epoxy resin compositions. Background Art
[0004] Epoxy thermoset composites and adhesives are known for their high strength and typically high glass transition temperature (Tg). Unfortunately, these useful materials are often brittle. While techniques for improving the fracture toughness of epoxy thermosets are well established, this remains an area of ongoing research.
[0005] One way to improve the toughness of epoxy systems is to use liquid carboxyl-terminated nitrile (CTBN) rubber in epoxy formulations. Liquid CTBN can be used directly as an additive, but this can lead to some stability issues due to the epoxy-acid reaction. In addition, if a pre-reaction of the epoxy resin and rubber has been performed, the resulting physical properties are usually better. A preferred way to do this is to adduct CTBN with an epoxy resin and use the adduct in a thermosetting material formulation. During curing, the rubber-containing adduct is incompatible with the cured epoxy matrix and forms separate low Tg elastomer discontinuous domains. These domains can improve the fracture toughness of thermosetting materials without significantly reducing modulus or Tg. In addition to liquid CTBN with different acrylonitrile contents, liquid and solid adducts of CTBN (made of liquid epoxy resin and solid epoxy resin, respectively) are easily commercially available. Due to the reactive carboxyl group at the end of the rubber, adducting with a difunctional epoxy resin mainly produces linear polymers. By careful selection of epoxy resin and the ratio of epoxy resin to CTBN, the adduct molecular weight and compatibility with the thermoset formulation components can be controlled. The use of liquid CTBN-based adducts is a well-established method for toughening epoxy thermosets.
[0006] One disadvantage of CTBN is that it is a viscous liquid. For example, Hypro1300X 13 from Huntsman is a CTBN with 26% acrylonitrile and a viscosity of 500,000 mPa·s at 27°C. Practical operations may require heating the CTBN to enable it to be transferred to a reaction vessel. Unfortunately, repeated heating of CTBN may increase viscosity and shorten its shelf life. Another disadvantage of CTBN is that the production method is particularly challenging. Therefore, there is almost no production equipment. In order to avoid supply interruptions, it is desirable to seek a substitute for epoxy resin-CTBN adducts.
[0007] A storage stable adduct is desirable because it separates the adduct synthesis from any thermoset compounding process. The adduct can be made in batch or continuous form at elevated temperatures typical for epoxy-acid reactions, with or without a catalyst to accelerate the reaction. Subsequent epoxy rubber adducts can be compounded at lower temperatures, such as for twin screw extrusion. Compounding at lower temperatures is desirable to avoid premature activation of the thermoset curing agent. By separating the manufacturing steps, a more efficient process can be used to produce rubber toughened epoxy thermosets.
[0008] Carboxylated solid nitrile rubber (XNBR) has been used to toughen thermosetting material formulations. CTBN has a low molecular weight and the carboxyl group is at the end of the polymer chain, while XNBR is different, with a high molecular weight and the carboxyl groups randomly spaced along the polymer chain. This can cause the adduct to gel during synthesis or storage. XNBR has been directly used in epoxy thermosetting resin formulations, which can cause formulation storage stability problems (due to the epoxy resin-acid reaction occurring over time at ambient temperature). In order to avoid gelation or storage stability problems, the adduct can be prepared in situ. This method requires long formulation mixing time to make the adduct, and limits the method and composition of making thermosetting material formulations.
[0009] Bascom et al. (WD Bascom, RY Ting, RJ Moulton, CK Riew and AR Siebert, J. of Mat. Sci., 16, 2657-2664, 1981) used CTBN-epoxy resin adducts and XNBR-epoxy resin adducts, alone and in combination, to demonstrate their effectiveness in improving the fracture toughness of epoxy thermosetting resins. When a liquid epoxy resin was used to make the XNBR adduct, a solvent was used, which required removal of the solvent before use. Only liquid epoxy resin was used in the adduct synthesis, and the material state (solid or liquid) of the adduct was not disclosed. In addition, the stability of the adduct was not mentioned.
[0010] U.S. Patent No. 3,707,583 discloses the use of carboxyl-containing nitrile rubber adducts in solid composite thermoset mixtures. Solid XNBR is included in the list of potential rubbers for adducting, but the examples only contain adducts based on liquid CTBN. The solid XNBR is used as an unreacted component in the thermoset mixture after compounding. No stability is mentioned.
[0011] U.S. Patent No. 6,013,730 discloses an adduct containing XNBR made in situ with a solvent. No attempt was made to isolate the adduct. Furthermore, only in situ adducts made with XNBR and liquid multifunctional epoxy resins having an average functionality of 3 or greater have been identified.
[0012] U.S. Patent No. 6,586,089 discloses the use of adducts containing CTBN. They mention solid adducts, but not solid rubber. In fact, lines 44 to 48 specify that the rubber also contains terminal groups that will react with epoxides to form covalent bonds therewith.
[0013] U.S. Patent No. 6,846,559 discloses the use of epoxy-elastomer adducts. Their preference is epoxy-CTBN, and they use solid epoxy and CTBN as examples. There are no examples of solid adducts made from epoxy and XNBR.
[0014] US Patent Publication No. 2004 / 0204551 discloses the preparation of solid adducts made from XNBR and solid epoxy resins in the absence of solvents. The inventors discuss the need for complete reaction to improve storage stability, but no stability data is provided for the adduct examples given.
[0015] US Patent No. 10,150,897 discloses the use of XNBR epoxy resin adducts having a molecular weight greater than 60,000 Da in impact toughened pumpable adhesives. All examples use a liquid adduct comprising a liquid epoxy resin and a small amount (about 5 wt%) of XNBR resin to produce a composition that can be used in a non-solid uncured composition.
[0016] It would therefore be desirable to have a solid epoxy-XNBR adduct that could be used as a single ingredient to toughen epoxy thermosets where the percentage of the adduct is not limited and does not create shelf life instabilities prior to curing. Summary of the invention
[0017] Storage-stable solid XNBR-epoxy resin adducts can be produced by carboxylated acrylonitrile-butadiene rubber with low acid content. These adducts provide toughening in epoxy thermosetting resin composites and adhesives. This paper teaches to relate to a solid, storage-stable epoxy resin composition, which comprises the reaction product of solid carboxylated acrylonitrile-butadiene rubber (XNBR) and epoxy-functional resin. The carboxylic acid content of this carboxylated acrylonitrile-butadiene rubber is less than about 2 % by weight carboxyl content.
[0018] The carboxyl content may be less than 1 wt %.The XNBR content may be at least 10 wt %.
[0019] The epoxy functional resin may be a solid.The epoxy functional resin may comprise a liquid epoxy resin.
[0020] The reaction product may be formed in the presence of a solvent. The reaction product may be formed in the absence of any solvent.
[0021] The epoxy resin composition may be adapted to foam upon exposure to a stimulus.The epoxy resin composition may be adapted to cure upon exposure to a stimulus.
[0022] When tested according to ISO 289, the XNBR may have a Mooney viscosity of 40 to 50 MU at 100°C.
[0023] The XNBR may have an acrylonitrile content of at least 30 wt%. The XNBR may have an acrylonitrile content of less than 40 wt%.
[0024] The composition may include more than one type of epoxy functional resin.
[0025] The composition may include at least two solid epoxy-functional resins.
[0026] The composition may include at least one solid epoxy-functional resin and at least one liquid epoxy-functional resin.
[0027] The composition may include a polymeric particle component.
[0028] The reaction product may form an adduct that is added to the composition.The reaction product may include a PVB component.
[0029] The ratio of XNBR to epoxy functional resin may be about 1 part XNBR: 3 parts epoxy functional resin to 1 part XNBR: 4 parts epoxy functional resin.
[0030] The teachings herein also relate to a foamable composition comprising a reaction product of a solid carboxylated nitrile rubber (XNBR) and an epoxy functional resin, a blowing agent, a curing agent, and optionally polymer particles.
[0031] The carboxylic acid content of the carboxylated nitrile rubber may be less than about 2 wt % carboxyl content.
[0032] Foaming agents can cause foaming after exposure to a stimulus.
[0033] The curing agent may cause curing upon exposure to a stimulus.
[0034] The carboxyl content may be less than 1% by weight.
[0035] The XNBR content may be at least 10% by weight.
[0036] The reaction product may be a solid at room temperature (eg, 20° C. to 25° C.).
[0037] The composition can have an increased tensile modulus compared to the same composition in which the reaction product is formed using CTBN instead of XNBR.
[0038] The composition can have an increased tensile strain at break compared to the same composition where CTBN is substituted for XNBR to form the reaction product.
[0039] The composition can have increased tensile strength at break compared to the same composition where CTBN is substituted for XNBR to form the reaction product.
[0040] The composition can have increased lap shear strength compared to the same composition where CTBN is substituted for XNBR to form the reaction product.
[0041] The composition can have an increased average peel strength compared to the same composition in which the reaction product is formed using CTBN instead of XNBR.
[0042] The present teachings also relate to the use of a composition according to any of the preceding items to adhere to an oil-coated substrate.
[0043] The present teachings also relate to the use of a composition according to any of the preceding items for adhering to a substrate in a cavity of a transport vehicle. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 Shown is a graph depicting melt flow index as a function of aging for exemplary materials according to the teachings herein.
[0045] Figure 2 Shown is a graph depicting melt flow index as a function of aging for exemplary materials according to the teachings herein.
[0046] Figure 3 Shown is a graph depicting melt flow index as a function of aging for exemplary materials according to the teachings herein. DETAILED DESCRIPTION
[0047] This teaching satisfies one or more of the above needs by the improved compositions and methods described herein. The explanation and description presented herein are intended to make other technical personnel in the art familiar with this teaching, its principles and its practical application. Those skilled in the art can modify and apply this teaching in its various forms so that it can best suit the needs of specific purposes. Therefore, the specific embodiments of this teaching set forth are not intended to be exhaustive or limit this teaching. Therefore, the scope of this teaching should not be determined with reference to the above description, but should be determined with reference to the full scope of the equivalents given by the attached claims and such claims. The disclosures of all articles and references (including patent applications and publications) are incorporated by reference for all purposes. Other combinations such as will be obtained from the attached claims are also possible, and the claims are also incorporated by reference in this written specification.
[0048] One aspect of the present teachings comprises a solid epoxy resin composition useful as a toughening agent in an epoxy resin formulation, comprising the reaction product of an XNBR having a low acid content and an epoxy resin. Preferably, the carboxylic acid content percentage (COOH weight percentage) in the XNBR is less than 2%, most preferably less than 1%. Sufficient acid content of the XNBR having a higher acid content may be consumed prior to reaction with the epoxy resin. However, it is preferred to use an XNBR having a low acid content to simplify the overall reaction process. Krynac X 146 from Arlanxeo is an exemplary XNBR having a carboxyl content of 0.5%.
[0049] Adducts can be made with liquid epoxy resins, but if it is desired to have a thermosetting component that is solid at room temperature, the adduct may require a solid additive to ensure that the finished adduct is a brittle solid. When reacting with XNBR, it is easier to use a solid epoxy resin because mixing of the ingredients before the reaction is simplified. The liquid epoxy resin can be part of the adduct reaction, or it can be added after the reaction to adjust the softening temperature of the adduct, or to change the ratio of epoxide to carboxyl functionality to make a greater excess of epoxide. In this article, we define an epoxy resin as a resin with at least two epoxy groups.
[0050] The adducts can be made in a batch or continuous process.Dual arm sigma mixers, single screw extruders, twin screw extruders and continuous kneaders are just some non-limiting examples of equipment that can be used to produce the adducts.
[0051] The adduct can be made at an elevated temperature of preferably 80°C to 250°C, more preferably 100°C to 200°C, most preferably 110°C to 165°C. The reaction is carried out in a molten state, and the minimum temperature must be above the softening point of the reaction mixture. A solvent can be used to reduce the softening point and viscosity of the reaction mixture. In order to make the finished adduct a brittle solid and produce a 100% solid formulated composition, the solvent may have to be removed. However, it is preferred to react in a molten state in the absence of a solvent. An epoxy resin-acid reaction catalyst known in the art can be used, but an epoxy resin-acid reaction catalyst is not necessary. Phosphines (such as triphenylphosphine), tertiary amines (such as dimethylbenzylamine), quaternary ammonium and phosphorus compounds (such as ethyltriphenylphosphine iodide) are a non-limiting list of potential catalysts.
[0052] The adduct mixture may contain inert fillers. Metal carbonates (such as calcium carbonate), silicates (such as wollastonite or bentonite (Garamite), clays (such as kaolin), fumed silica are a non-limiting list of inorganic fillers. Thermoplastic polymers such as polyvinyl butyral, phenoxy resins, polycarbonates and ethylene copolymers and terpolymers may also be part of the mixture. Other common thermosetting ingredients such as pigments, UV absorbers or stabilizers, free radical scavengers, antioxidants are allowed.
[0053] The compositions described herein may include at least one type of polymer particles. Such polymer particles may be used to improve fracture toughness (G 1C ), peel resistance and impact resistance. As used herein, the term "polymer particles" as with any other component of the present invention may include one or more types of polymer particles. Various types of polymer particles may be used in the practice of the present invention, and typically include one or more elastomers. The polymer particles are typically preferably at least 4% by weight of the activatable material, more typically at least 7% by weight, even more typically at least 10% by weight, even more typically at least 13% by weight, and the polymer particles are also preferably less than 90% by weight of the activatable material, more typically less than 40% by weight, even more typically less than 30% by weight, although higher or lower amounts may be used in specific embodiments.
[0054] The polymer particles may include one or more core / shell polymers that may be pre-dispersed in an epoxy resin. The process of forming the core-shell material in a liquid epoxy resin avoids agglomeration of the core-shell particles, which is common in "dry" core-shell polymer particles (e.g., agglomeration may occur during the drying process). Examples of products made by this process may be described in one or more of U.S. Patents Nos. 3,984,497; 4,096,202; 4,034,013; 3,944,631; 4,306,040; 4,495,324; 4,304,709; and 4,536,436. The polymer particles may be formed by an emulsion polymerization process. The process may include adding a solvent to the resin. Because the resin / solvent and water are incompatible, when the core-shell particles move into the resin, water settles out of the material, reducing agglomeration. Alternatively, a high-speed dispersion device may effectively depolymerize the core / shell material. However, surfactants may remain after the core / shell material is spray dried or agglomerated. This residual surfactant may be detrimental to the material's ability to withstand environmental exposure conditions involving water, such as salt spray and moisture. Materials that have not been exposed to environmental exposure conditions generally do not show differences between dry core-shell and liquid core-shell masterbatches, as long as the dry material is fully deagglomerated.
[0055] As used herein, the term core-shell polymer can refer to a polymer material, wherein a majority of it (e.g., greater than 30 wt%, 50 wt%, 70 wt% or more) can include a first polymer material (i.e., a first or core material), which can be substantially completely encapsulated by a second polymer material (i.e., a second or shell material). As used herein, the first polymer material and the second polymer material can include one, two, three or more polymers, which are combined and / or reacted together (e.g., sequential polymerization), or can be a part of a separate or identical core / shell system. The core / shell polymer should be compatible with the formulation, and preferably has a tough core and a rigid shell that has good adhesion to other components of the activatable material.
[0056] Examples of useful core / shell polymers include, but are not limited to, those sold under the trade name Kane Ace, commercially available from Kaneka. Particularly preferred grades of Kane Ace core / shell are sold under the models MX-257 and M711 or Clear Strength E-950 available from Arkema. The core-shell polymer particles may be from about 4% to about 20% by weight of the activatable material.
[0057] These compositions may include a curing agent in the range of about 0.1% to about 5.0% by weight of the material. The material may include a blowing agent. The blowing agent may be a physical blowing agent. The blowing agent may be a chemical blowing agent. The material may include a blowing agent in the range of about 0.1% to about 5.0% by weight of the material. The material may include a flexibilizer.
[0058] The blowing agent may include one or more nitrogen-containing groups, such as amides, amines, etc. Non-limiting examples of suitable blowing agents include azodicarbonamide, dinitrosopentamethylenetetramine, 4,4 i -oxy-bis-(benzenesulfonyl hydrazide), trihydrazide triazine and N,N i -Dimethyl-N,N i -dinitrosoterephthalamide. The material may include a physical blowing agent, including but not limited to, such as available from Nouryon Alternatively, the material can be obtained from Trexel Manufacturing process.
[0059] Promotor for blowing agent can also be provided in the composition of the present invention. Various promoters can be used to increase the rate at which blowing agent forms inert gas and / or reduce the temperature at which blowing agent forms inert gas. A preferred blowing agent promoter is a metal salt or an oxide, for example a metal oxide, such as zinc oxide. Other preferred promoters include modified and unmodified thiazoles, ureas and imidazoles.
[0060] Curing agent is likely to help this paper composition solidify by polymer, epoxy resin or the crosslinking of both. Curing agent is also likely to help the composition to be advanced or chain extended. Useful categories of curing agent are selected from the following materials: aliphatic amine or aromatic amine or their respective adducts, amide-amine, polyamide, alicyclic amine, anhydride, polycarboxylic acid polyester, isocyanate, phenol-based resin (for example phenol or cresol novolac resin, copolymer (such as phenol terpene, those of polyvinyl phenol or bisphenol-A formaldehyde copolymer), bishydroxyphenyl alkane etc.) or its mixture. Particularly preferred curing agent includes modified and unmodified polyamine or polyamide, such as triethylenetetramine, diethylenetriamine, tetraethylenepentamine, cyanoguanidine, dicyandiamide etc.
[0061] One or more curing agents and / or curing agent accelerators may be added to the composition. The amount of curing agent and curing agent accelerator may vary widely within the composition, depending on the desired cure rate, desired cell structure, desired composition structural properties, etc. An exemplary range of curing agent or curing agent accelerator present in the composition is from about 0.001 wt % to about 7 wt %.
[0062] An accelerator for the curing agent (eg, a modified or unmodified urea such as methylene diphenyl bisurea, imidazole, or a combination thereof) may also be provided for use in preparing the composition.
[0063] Examples of suitable curing agents may be polyamine curing agents such as those available from Evonik Resource Efficiency GmbH. CG 1200 (ie, micronized dicyandiamide). An example of a suitable curing accelerator may be a substituted urea accelerator such as available from Huntsman Corporation U-52M (ie, phenyl substituted urea).
[0064] The compositions described herein may also include one or more reinforcing components. Preferably, the reinforcing components include materials that are generally not reactive with other components present in the composition. It is contemplated that the reinforcing components may also impart properties such as strength and impact resistance to the composition.
[0065] The example of reinforcing component includes wollastonite, silicon dioxide, diatomite, glass, clay (for example, including nano clay), glass beads or microspheres, glass, carbon fiber or ceramic fiber, nylon, aramid fiber or polyamide fiber etc. One or more reinforcing components can be selected from mineral reinforcement materials, such as diatomite, clay (for example, including nano clay), pyrophyllite, sauconite, soapstone, nontronite, wollastonite or montmorillonite. Reinforcing component can include silicon dioxide and / or calcium mineral reinforcement materials. Reinforcing component can include glass, glass beads or microspheres, carbon fiber or ceramic fiber, nylon, aramid fiber or polyamide fiber (for example Kevlar). Reinforcing component can be wollastonite. Reinforcing component can be the fiber with aspect ratio of about 20:1 to about 3:1. Reinforcing component can be the fiber with aspect ratio of about 15:1 to about 10:1. Reinforcing component can be the fiber with aspect ratio of about 12:1. The reinforcing component has the potential to improve the first physical characteristic while substantially avoiding any significant deleterious effects on the second physical characteristic. As an example, the selected reinforcing component can improve the overall tensile modulus of the composition while still having minimal deleterious effects on the failure strain. The composition can also include one or more fillers, including pigments or colorants, calcium carbonate, talc, silicate minerals, vermiculite, mica, etc.
[0066] When used, the reinforcing component in the composition can range from 10% by weight or less to 90% by weight or more of the composition, but more typically from about 20% by weight to 55% by weight of the composition. According to some embodiments, the composition can include from about 0% by weight to about 30% by weight, more preferably slightly less than 10% by weight of the reinforcing component.
[0067] It is contemplated that virtually any additional chemicals, materials, or other substances may be added to the activatable material so long as they are suitable for the composition and for the selected application of the composition.
[0068] Other additives, agents or performance modifiers may also be included in the composition as desired, including but not limited to anti-UV agents, flame retardants, heat stabilizers, colorants, processing aids, lubricants, and the like.
[0069] Example
[0070] The materials used in the examples are listed in Table A below:
[0071] Table A
[0072]
[0073]
[0074] Example 1: 450 parts of Krynac X 146 were added to a jacketed double-arm mixer that was temperature-controlled by a hot oil temperature control unit (TCU) set at 350°F and crushed for several minutes. Then 675 parts of YD-017 solid epoxy resin were added at once, and the system was mixed until the epoxy resin melted and formed a homogeneous mixture. Then 675 parts of YD-019 epoxy resin were added in 4 portions over 5 minutes. After mixing for 50 minutes, the TCU set point was reduced to 340°F and the mixture was mixed for another 3 hours. This maintained the mixture temperature at 315°F to 325°F. Next, the TCU set point was reduced to 300°F and 200 parts of YD-128 liquid epoxy resin were added over 5 minutes. Mixing was continued for 30 minutes. The TCU set point was reduced to 250°F, and the adduct was removed from the mixer and quickly cooled to room temperature. The material was a brittle solid after cooling.
[0075] Example 2: 450 parts of Krynac X 160 solid rubber were added to the apparatus described in Example 1 with the TCU set at 330°F and pulverized for about 35 minutes. Then 675 parts of YD-017 solid epoxy resin were added in one go and the system was mixed until the epoxy resin melted and formed a homogenous mixture. Then 675 parts of YD-019 epoxy resin were added over a 5 minute time span. After mixing for an additional 10 minutes, the mixture appeared to be homogenous. After mixing for 1 hour, the TCU set point was reduced to 340°F and the mixture was mixed for an additional 3 hours. This maintained the mixture temperature at 315°F to 325°F. Next, the TCU set point was reduced to 300°F and 200 parts of YD-128 liquid epoxy resin were added over a 5 minute time span. Mixing was continued for 60 minutes. The TCU set point was reduced to 250°F and the adduct was removed from the mixer and rapidly cooled to room temperature. The material was a brittle solid after cooling to room temperature.
[0076] Example 3: To the apparatus described in Example 1 with the TCU set at 330°F was added 630 parts of Krynac X 146 and crushed for several minutes. Then 990 parts of YD-017 were added over several minutes to obtain a homogenous mixture. Mixing was continued for 3 hours. The TCU set point was reduced to 300°F and 180 parts of YD-128 were added over 13 minutes. Mixing was continued for 60 minutes, after which the TCU set point was reduced to 250°F and the mixture was removed from the mixer. The mixture was rapidly cooled to obtain a friable solid.
[0077] Example 4: 500 parts of Krynac X 146 were added to the apparatus described in Example 1 with the TCU set at 250°F and crushed for 5 minutes. Subsequently, 750 parts of Guodu KD-214C epoxy resin were added over 8 minutes to obtain a homogenous mixture. Next, the TCU set point was increased to 270°F and an additional 750 parts of KD-214C were added over 8 minutes. The TCU set point was then increased to 320°F and mixing continued for 53 minutes. Next, the TCU set point was increased to 330°F and mixing continued for 150 minutes. The material was then removed from the mixer and rapidly cooled to obtain a friable solid.
[0078] Example 5: To the mixer described in Example 1 at a TCU set point of 350°F, 450 parts of Krynac X146 were added and crushed for three minutes. Then 675 parts of YD-017 were added over a 5 minute time span. Next, 675 parts of YD-019 were added over a 5 minute time span to obtain a homogenous mixture. After mixing for 4 hours, the TCU set point was reduced to 300°F and 200 parts of YD-128 were added over a 5 minute time span. The material was mixed for another 15 minutes. The TCU set point was then reduced to 275°F and 10 parts of Irganox 1010 antioxidant were added. Mixing was continued for 5 minutes. The adduct was then removed from the mixer and rapidly cooled to obtain a friable solid.
[0079] Example 6: To the mixer described in Example 1 at a TCU set point of 350°F, 450 parts of Krynac X146 were added and crushed for three minutes. Then 675 parts of YD-017 were added over a 5 minute time span. Next, 675 parts of YD-019 were added over a 5 minute time span to obtain a homogenous mixture. Then 200 parts of YD-128 were added over a 5 minute time span. After mixing for 1 hour, the TCU set point was reduced to 340°F. The material was mixed for an additional 3 hours. The TCU set point was then reduced to 250°F. The material was mixed for an additional 20 minutes. The adduct was then removed from the mixer and rapidly cooled to obtain a friable solid.
[0080] Example 7: In a manner similar to that described in Example 1, an adduct having the following composition was prepared by a single addition. Thermoplastic polyvinyl butyral (PVB) was added after the introduction of YD-128 and mixed for several minutes to ensure a homogeneous mixture. The mixture was then removed from the mixer and rapidly cooled to room temperature to obtain a brittle solid. The composition is shown in Table B below.
[0081] Table B
[0082]
[0083]
[0084] Example 8: 9800 parts of Krynac X146 were added to the apparatus described in Example 1 with the TCU set to 320°F and crushed for 10 minutes. Subsequently, 4200 parts of Guodu KD-214C epoxy resin were added over 15 minutes to obtain a homogenous mixture. Mixing was continued for more than 150 minutes while adjusting the TCU set point to maintain a mixture temperature of 280°F. The material was then removed from the mixer and rapidly cooled to obtain a brittle solid.
[0085] Example 9: To the same apparatus described in Example 1 with the TCU set to 180°F, 480 parts of Nipol 1472X were added and pulverized for about 5 minutes. Then 760 parts of DER 661 solid epoxy resin were added over 4 minutes. The TCU set point was increased to 200°F and an additional 760 parts of DER 661 were added over 13 minutes to make a homogenous dispersion. The TCU set point was increased to 300°F. After 1 hour, the mixture formed a gel. This example shows that even if the amount of epoxide functionality of the lower molecular weight epoxy resin DER 661 is increased, the higher acid functionality of Nipol 1472X will result in an unstable adduct. See Table A of US2004 / 0204551, where similar compositions were formed. This example indicates that the compositions listed in Table A of US2004 / 0204551 are not fully reacted and, if fully reacted, will gel.
[0086] To illustrate storage stability, the melt flow index of the adduct of Example 5 stored at ambient temperature was monitored (Dynisco, Model LMI 4000, at 150° C., 2.16 kg). Figure 1 The melt index decreased only slightly. Typically, a decrease in melt index over time indicates that the polymer continues to advance or react. Similarly, the robust storage stability of Example 7 is shown in Figure 2 middle. Figure 1 and Figure 2 The storage stability of solid rubber adducts utilizing higher molecular weight epoxy resins is demonstrated. Figure 3 The storage stability of Example 8 is shown, indicating that even with lower molecular weight epoxy resins, solid rubber adducts made with rubbers having low acid content are stable.
[0087] The compositions of the two solid adducts (one from liquid CTBN and one from solid XNBR, made in a manner similar to Example 1) are as follows. In Example 10, YD-017 and YD-019 were added first and melted before adding Hypro 1300x13. The compositions are shown in Table C below.
[0088] Table C
[0089]
[0090] The adducts of Examples 10 and 11 were formulated into foamable structural adhesives having the following compositions shown in Table D (Examples 12 and 13).
[0091] Table D
[0092] Material Example 12 Composition (wt%) Example 13 Composition (wt%) Example 10 54.97 Embodiment 11 54.97 TMEP70ASP 10.00 10.00 KaneAce MX257 25.00 25.00 Kevlar Masterbatch* 5.00 5.00 Cellcom AC7001 2.00 2.00 Amicure CG-325G 2.40 2.40 Omicure U52M 0.60 0.60 pigment 0.03 0.03 total 100.00 100.00
[0093] *20% chopped and fibrillated aramid fibers are compounded with 80% Type 1 epoxy resin.
[0094] The foamed adhesives of Examples 12 and 13 cured at 163°C for 30 minutes were evaluated to give the following properties as shown in Table E.
[0095] Table E
[0096]
[0097]
[0098] *0.030” EG60, test speed: 254 mm / min, bond line 3 mm; **0.060” EG60, test speed: 50.4 mm / min, bond line 1.5 mm, 2.5 to 3.0 mg / in 2 , 61MAL HCL;
[0099] Table E shows that XNBR based adducts provide comparable or better performance when compared to CTBN based adducts. Specifically, the peel strength of Example 13 at slightly lower rubber elastomer content indicates that the XNBR adduct has comparable or better toughness.
[0100] Unless otherwise stated, the size and geometry of the various structures described herein are not intended to limit the present invention, and other sizes or geometries are also possible. Multiple structural components can be provided by a single integrated structure. As a selection, a single integrated structure can be divided into a plurality of independent components. In addition, although it is possible to describe features of the present invention only in the context of one of the illustrated embodiments, for any given application, this feature can be combined with one or more other features of other embodiments. It can also be understood from the above that the manufacture of the unique structure of this article and its operation also constitute a method according to the present invention.
[0101] Preferred embodiments of the present invention have been disclosed. However, one of ordinary skill in the art will recognize that certain modifications would fall within the teachings of this invention. Therefore, the appended claims should be studied to determine the true scope and content of this invention.
[0102] The explanation and description given herein are intended to familiarize other technical personnel in the art with the present invention, its principles and its practical application. Those skilled in the art can modify and apply the present invention in its various forms, and these various forms can be most suitable for the requirements of specific uses. Therefore, the specific embodiments of the present invention described are not intended to be exhaustive or limit the present invention. Therefore, the scope of the present invention should not be determined with reference to the above description, but should be determined with reference to the full scope of the equivalents given by the attached claims and such claims. The disclosures of all articles and references (including patent applications and publications) are incorporated by reference for all purposes. Other combinations such as will be obtained from the attached claims are also possible, and the claims are also incorporated by reference in this written specification.
Claims
1. A solid, storage-stable epoxy resin composition, the solid, storage-stable epoxy resin composition comprising the reaction product of: (i) solid carboxylated nitrile rubber (XNBR); and (ii) epoxy functional resin; The carboxylic acid content of the carboxylated nitrile rubber is less than about 2% by weight carboxyl content.
2. The composition according to claim 1, wherein the carboxyl content is less than 1 wt%.
3. A composition according to claim 1 or claim 2, wherein the XNBR content is at least 10 wt%.
4. The composition of any one of the preceding claims, wherein the epoxy functional resin is a solid.
5. The composition of any one of the preceding claims, wherein the epoxy-functional resin comprises a liquid epoxy resin.
6. The composition of any one of the preceding claims, wherein the reaction product is formed in the presence of a solvent.
7. The composition of any one of the preceding claims, wherein the reaction product is formed in the absence of any solvent.
8. The composition of any one of the preceding claims, wherein the epoxy resin composition is adapted to foam upon exposure to a stimulus.
9. The composition of any one of the preceding claims, wherein the epoxy resin composition is adapted to cure upon exposure to a stimulus.
10. The composition according to any one of the preceding claims, wherein the XNBR has a Mooney viscosity of 40 to 50 MU at 100°C when tested according to ISO 289.
11. The composition according to any one of the preceding claims, wherein the XNBR has an acrylonitrile content of at least 30 wt%.
12. The composition according to any one of the preceding claims, wherein the XNBR has an acrylonitrile content of less than 40 wt%.
13. The composition of any one of the preceding claims, wherein the composition comprises more than one type of epoxy functional resin.
14. The composition of any one of the preceding claims, wherein the composition comprises at least two solid epoxy-functional resins.
15. The composition of any one of the preceding claims, wherein the composition comprises at least one solid epoxy functional resin and at least one liquid epoxy functional resin.
16. A composition according to any preceding claim, wherein the composition comprises a polymeric particle component.
17. A composition according to any one of the preceding claims, wherein the reaction product forms an adduct which is added to the composition.
18. The composition of any one of the preceding claims, wherein the reaction product comprises a PVB component.
19. The composition of any of the preceding claims, wherein the ratio of XNBR to epoxy functional resin is from about 1 part XNBR: 3 parts epoxy functional resin to 1 part XNBR: 4 parts epoxy functional resin.
20. A foamable composition comprising: (i) the reaction product of a solid carboxylated nitrile rubber (XNBR) and an epoxy functional resin; (ii) a blowing agent; (iii) a curing agent; and (iv) Optional polymer particles.
21. The composition of claim 20, wherein the carboxylic acid content of the carboxylated nitrile rubber is less than about 2 wt% carboxyl content.
22. The composition of claim 20 or 21, wherein the foaming agent causes foaming upon exposure to a stimulus.
23. The composition of any one of claims 20 to 22, wherein the curing agent causes curing upon exposure to a stimulus.
24. The composition of any one of claims 20 to 23, wherein the carboxyl content is less than 1 wt%.
25. The composition according to any one of claims 20 to 24, wherein the XNBR content is at least 10 wt%.
26. The composition of any one of claims 20 to 25, wherein the epoxy functional resin is a solid.
27. The composition of any one of claims 20 to 26, wherein the epoxy functional resin comprises a liquid epoxy resin.
28. The composition of any one of claims 20 to 27, wherein the reaction product is formed in the presence of a solvent.
29. The composition of any one of claims 20 to 27, wherein the reaction product is formed in the absence of any solvent.
30. The composition of any one of claims 20 to 29, wherein the XNBR has a Mooney viscosity of 40 to 50 MU at 100°C when tested according to ISO 289.
31. The composition of any one of claims 20 to 30, wherein the XNBR has an acrylonitrile content of at least 30 wt%.
32. The composition of any one of claims 20 to 31, wherein the XNBR has an acrylonitrile content of less than 40 wt%.
33. The composition of any one of claims 20 to 32, wherein the composition comprises more than one type of epoxy functional resin.
34. The composition of any one of claims 20 to 33, wherein the composition comprises at least two solid epoxy functional resins.
35. The composition of any one of claims 20 to 34, wherein the composition comprises at least one solid epoxy functional resin and at least one liquid epoxy functional resin.
36. A composition according to any one of claims 20 to 35, wherein the composition comprises a polymer particle component.
37. The composition of any one of claims 20 to 36, wherein the reaction product forms an adduct that is added to the composition.
38. The composition of any one of claims 20 to 37, wherein the reaction product comprises a PVB component.
39. The composition of any one of claims 20 to 38, wherein the ratio of XNBR to epoxy functional resin is from about 1 part XNBR: 3 parts epoxy functional resin to 1 part XNBR: 4 parts epoxy functional resin.
40. The composition of any one of claims 20 to 39, wherein the reaction product is a solid at room temperature (eg, 20°C to 25°C).
41. A composition according to any one of the preceding claims, wherein The composition has an increased tensile modulus compared to the same composition but with CTBN substituted for XNBR to form the reaction product.
42. A composition according to any one of the preceding claims, wherein The composition has an increased tensile strain at break compared to the same composition wherein CTBN is substituted for XNBR to form the reaction product.
43. A composition according to any one of the preceding claims, wherein The composition has increased tensile strength at break compared to the same composition wherein CTBN is substituted for XNBR to form the reaction product.
44. A composition according to any one of the preceding claims, wherein The composition has increased lap shear strength compared to the same composition wherein CTBN is substituted for XNBR to form the reaction product.
45. A composition according to any one of the preceding claims, wherein The composition has an increased average peel strength compared to the same composition wherein CTBN is substituted for XNBR to form the reaction product.
46. Use of a composition according to any preceding claim to adhere to an oil coated substrate.
47. Use of a composition according to any preceding claim to adhere to a substrate in a cavity of a transport vehicle.
Citation Information
Patent Citations
Adhesive compositions, manufacture and use thereof
US10150897B2
Epoxy / elastomer adduct, method of forming same and materials and articles formed therewith
US20040204551A1
adhesive
US3707583A
Acrylate-styrene-acrylonitrile composition and method of making the same
US3944631A
Acrylic modifiers for polycarbonamides
US3984497A